Gender and Business History - Kwolek-Folland, Angel (Enterprise & Society, 2001)
In response to an invitation from the editor of Enterprise & Society, last year David Sicilia and I put out a call for papers for a special issue of the journal that would focus on gender and business history. The call elicited twenty-five submissions, an impressive array of scholarship from authors who addressed the subject from a range of theoretical and disciplinary approaches. From these submissions, we chose the four articles that appear in this volume and three others that will be published in the next issue of Enterprise & Society (June 2001). We made our final selections on the basis of thematic, national, and organizational representativeness and on the ways in which the articles complemented each other and revealed aspects of the “state of the field.” Let me thank the more than fifty referees who generously read and commented anonymously on the original submissions. I enjoyed working with them, with the authors, and with David in this communal endeavor.
Keywords: Business History and gender